ABSTINENSI SEKSUAL REMAJA SMP DI KOTA TANGERANG SELATAN - Mizna Sabilla; Nurfadhilah Nurfadhilah (Puslitbang Upaya Kesehatan Masyarakat, 2020)
Abstract Background: Indonesia is projected to experience the peak of the demographic bonus in 2030. The demographic bonus can turn into a burden if adolescents who are successors are not qualified. Adolescent who are supposed to be 100% absent from sex actually showed an unsatisfactory proportion in several areas. Objective: This study aimed to describe abstinence behavior among adolescents at junior high school in South Tangerang City. Method: This study used a cross sectional design. The study population was junior high school students by selecting 25 junior high schools as the sample. The number of samples were 165 students who were taken incidentally. Data was collected from December 2019 to January 2020 by filling out a questionnaire through interviews. Result: The proportion of abstinence among junior high school students was 80%. The highest abstinence was occurred among adolescent boys and aged 12 years. Most of them carried out positive activities such as art, organization, regular worship, regular exercise, and courses. Most of them admitted that they did not feel seduced, coerced and threatened to have sexual activity. When a sensitive part of the body was touched, respondents acted assertively by refusing, shouting, and hitting. Conclusion: Sexual abstinence among adolescents at junior high school in South Tangerang needs to be increased. Understanding the importance of abstinence needs to be given to adolescents from the onset of puberty by parents, school environment (school organizations and PIKR) and community (religious organizations). Keywords: Sexual abstinence, Adolescent at Junior High School, South Tangerang Abstrak Latar belakang: Indonesia akan mengalami puncak bonus demografi pada tahun 2030. Bonus demografi dapat berbalik menjadi beban apabila remaja yang menjadi penerus tidak berkualitas. Remaja yang seharusnya 100 persen absen seks justru menunjukkan proporsi yang tidak menggembirakan di beberapa wilayah. Tujuan: Penelitian ini bertujuan untuk mengetahui gambaran perilaku abstinensi pada remaja usia SMP di Kota Tangerang Selatan. Metode: Penelitian menggunakan desain cross-sectional. Populasi penelitian adalah remaja usia SMP dengan memilih 25 SMP sebagai sampel. Jumlah sampel sebanyak 165 siswa/siswi yang diambil secara insidentil. Pengumpulan data dilakukan pada Desember 2019 sampai Januari 2020 dengan pengisian kuesioner melalui wawancara. Hasil: Proporsi abstinensi seksual remaja SMP sebesar 80 persen. Abstinensi tertinggi dialami oleh remaja laki-laki dan usia 12 tahun. Sebagian besar melakukan kegiatan positif seperti seni, berorganisasi, rutin beribadah, rutin berolahraga, dan mengikuti seminar/kursus. Sebagian besar responden mengaku tidak pernah merasa dirayu, dipaksa dan diancam untuk melakukan aktivitas seksual. Apabila bagian tubuh sensitifnya disentuh responden melakukan tindakan asertif dengan menolak, berteriak, dan memukul. Kesimpulan: Abstinensi seksual remaja SMP di Tangerang Selatan harus ditingkatkan. Orang tua perlu menjaga dan mengawasi pergaulan anaknya. Pemahaman agama dan pentingnya abstinensi perlu diberikan kepada remaja semenjak awal pubertas dari orang tua, lingkungan sekolah dan masyarakat melalui organisasi keagamaan dan PIKR Kata kunci: Abstinensi seksual, Remaja SMP, Tangerang Selatan